2010
DOI: 10.1074/jbc.m109.072157
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Bifunctional Pyranose-Furanose Mutase from Campylobacter jejuni 11168

Abstract: UDP-galactopyranose mutases (UGM) are the enzymes responsible for the synthesis of UDP-galactofuranose (UDP-Galf) from UDP-galactopyranose (UDP-Galp). The enzyme, encoded by the glf gene, is present in bacteria, parasites, and fungi that express Galf in their glycoconjugates. Recently, a UGM homologue encoded by the cj1439 gene has been identified in Campylobacter jejuni 11168, an organism possessing no Galf-containing glycoconjugates. However, the capsular polysaccharide from this strain contains a 2-acetamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 60 publications
1
39
0
Order By: Relevance
“…Previously, it has been shown that coupling glycosyltransferases with the mutase has been effective in overcoming the low yield associated with Gal p to Gal f turnover. 40-43 In this report, a large excess of UDP-Gal p was used, so it is not clear how much this coupling benefits the low turnover of the WcfM reaction. We have now established the complete in vitro reconstitution of the repeat unit of CPSA using key fluorescent isoprenoid probes.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, it has been shown that coupling glycosyltransferases with the mutase has been effective in overcoming the low yield associated with Gal p to Gal f turnover. 40-43 In this report, a large excess of UDP-Gal p was used, so it is not clear how much this coupling benefits the low turnover of the WcfM reaction. We have now established the complete in vitro reconstitution of the repeat unit of CPSA using key fluorescent isoprenoid probes.…”
Section: Discussionmentioning
confidence: 95%
“…It catalyzes a key step in the degradation of both flavonols (via flavanonols) and flavones (via flavanones). Bifunctionality is widespread among bacterial enzymes due to their compact genomes (34)(35)(36)(37)(38). However, CHI is not a classical bifunctional enzyme, as it does not utilize two different domains for catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, examination of the HPLC data revealed that both mutants were capable of interconverting UDP-Glc p /UDP-Gal p . Unfortunately, interconversion for the UDP-Glc p NAc/UDP-Gal p NAc pair by AnGALE was not separable by HPLC and as a result, the reaction was coupled with the enzyme UDP-N-acetylgalactopyranose mutase (UNGM) [69] to form a measurable product (UDP-Gal f NAc). UNGM functions in a similar manner to UGM catalyzing the production of UDP-Gal f NAc from precursor UDP-Gal p NAc.…”
Section: Resultsmentioning
confidence: 99%